2011
DOI: 10.1097/sle.0b013e31821db7b2
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes After Laparoscopic Cholecystectomy in Children With Biliary Dyskinesia

Abstract: Our objectives were to determine the prevalence of biliary dyskinesia (BD) as an indication for cholecystectomy in children and to identify presenting clinical findings and optimal ejection fraction (EF) associated with the resolution of symptoms after surgery. We conducted a retrospective review of medical records of 212 pediatric patients who underwent cholecystectomy from August, 1998 to November, 2006. Patients who met criteria for BD had their short-term outcomes examined by record review and their long-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 0 publications
2
37
0
Order By: Relevance
“…While the results favored cholecystectomy, the control group did not receive any active therapy and did not show any improvement, a highly unusual finding in functional disorders [13]. The results also differ from reported outcomes in BD, which are more variable with decreasing success rates after longer follow-up time and which include response rates exceeding 50 % in patients who did not undergo surgery [12, 1428]. …”
Section: Introductionmentioning
confidence: 97%
“…While the results favored cholecystectomy, the control group did not receive any active therapy and did not show any improvement, a highly unusual finding in functional disorders [13]. The results also differ from reported outcomes in BD, which are more variable with decreasing success rates after longer follow-up time and which include response rates exceeding 50 % in patients who did not undergo surgery [12, 1428]. …”
Section: Introductionmentioning
confidence: 97%
“…Given the increase in the incidence of cholecystectomy for biliary dyskinesia, there is interest in identifying predictive factors to determine which pediatric patients are more likely to benefit from cholecystectomy. Predictive factors for long-term symptom improvement after cholecystectomy for biliary dyskinesia have not been consistently identified [6,8,9]. One study has suggested that obese patients are less likely to derive benefit from cholecystectomy [16], but in the present study, obese patients were equally as likely as nonobese patients to benefit from cholecystectomy at early and long-term follow-up.…”
Section: Discussionmentioning
confidence: 44%
“…Existing literature supports several different EF cutoffs to diagnose biliary dyskinesia [4,9,12,17,19,20]. In children, HIDA scans have only been reported to be predictive of symptom relief in patients with very low EFs [8,9,16,21,22]. Our study also investigated the ability of FUS to diagnose biliary dyskinesia.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations